Mitigation Training in Preparation of Face-to-face Learning in Schools under Health Reviews during Pandemic - Stujanna, Endin Nokik (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The Covid-19 pandemic has hit the whole world, including Indonesia. This pandemic has greatly impacted all sectors, including education. Online learning process has many obstacles and brings serious impacts. As a result, the policy of implementing face-to-face learning during pandemic was issued. Mitigation training is very important. This training attempts to discuss face-to-face learning at schools and obtain representative opinions regarding the preparation and consideration based on health reviews in relevant with the latest research and recommendations. This online training was held with the participants involving teachers and parents (n=219) from Elementary and Junior High School of Al-azhar SummareconSerpong, and has been shared on YouTube platform. Several opinions were obtained from parents who disagree with face-to-face learning’s idea. It also increased the knowledge regarding mitigation of face-to-face learning at schools. The education aspect is indeed something that must become a priority, but without compromising the student’s health aspect.